Bibliometric Analysis and Visualization Harm Reduction in Indonesia Indexed in Scopus - Yeyen Subandi; Achmad Nurmandi; Zuly Qodir; Hasse Jubba; Titin Purwaningsih; Tri Hastuti Nur Rochima (PT FORMOSA CENDEKIA GLOBAL, 2022)
Harm Reduction is a program to reduce the harm of narcotics for injecting drug users. The Harm Reduction (HR) program in Indonesia was initiated in 1999 with assistance and financial support from international donor agencies that lead to policy or program implementation. 9 components of Harm Reduction are still being implemented in Indonesia. The current study was conducted to analyze the bibliometric characteristics and trends of articles on Harm Reduction in Indonesia. This study uses VOSviewer affiliate analysis to visualize and analyze trends in the form of bibliometric maps. VOSviewer can also create publication maps, country maps, or journal maps based on shared citation networks or create keyword maps based on their networks. All data is taken from the Scopus database. Articles from 1999 to 2021 in 41 journals indexed by Scopus with a total of 67 documents. Research on Harm Reduction in Indonesia in the last five years has only one significant increase, namely in 2019 with 10 article documents.Harm Reduction is a program to reduce the harm of narcotics for injecting drug users. The Harm Reduction (HR) program in Indonesia was initiated in 1999 with assistance and financial support from international donor agencies that lead to policy or program implementation. 9 components of Harm Reduction are still being implemented in Indonesia. The current study was conducted to analyze the bibliometric characteristics and trends of articles on Harm Reduction in Indonesia. This study uses VOSviewer affiliate analysis to visualize and analyze trends in the form of bibliometric maps. VOSviewer can also create publication maps, country maps, or journal maps based on shared citation networks or create keyword maps based on their networks. All data is taken from the Scopus database. Articles from 1999 to 2021 in 41 journals indexed by Scopus with a total of 67 documents. Research on Harm Reduction in Indonesia in the last five years has only one significant increase, namely in 2019 with 10 article documents.